THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS (AIS), HUMAN CAPITAL, AND CUSTOMER CAPITAL ON SME PERFORMANCE IN PATI DISTRICT - Winarsih, Winarsih; Istianah, Siti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
SMEs are supporting the economy of the country, but there are still many obstacles faced by SME actors, one of which is access to information to examine the effect of accounting information systems, human capital, and customer capital on the performance of SMEs. This research uses a quantitative approach, the research data is primary data using questionnaires and population collection as well as research samples from SME actors in Pati Regency. The method of determining the sample is purposive sampling. The technique used to test the hypothesis is multiple linear regression analysis using the SPSS application.